The Ford Foundation at work: philanthropic choices, methods, and styles - Magat, Richard (New York : Plenum Press, 1979)
This publication is meant as a step to account for the work the Ford Foundation does. The foundation is required by law to record publically what they do.
Includes bibliographical references and index.
rpm 22/01/2019
Loans
Keywords: Ford Foundation; Philanthropic